Shaking table study on the seismic performance of an Iranian traditional Un-Reinforced Masonry (URM) building. (October 2020) - Shabdin, M.; K.A. Attari, Nader; Zargaran, M.
Abstract: Shaking table experiment for considering the seismic performance of an existing un-reinforced masonry (URM) building with Jack-arch flooring system was performed. This structural system is one of the most common traditional structures, especially in existing traditional school buildings in Iran. The study involved seismic and dynamic identification tests on one model before and after being modified, including URM brick building with two different floor behavior. In the first model, steel tie beams and steel rods were used, according to the recommendation of Iranian Code of Practice for Seismic Resistant Design of Buildings (Standard-2800), to improve the integrity between steel joists and have a stiff diaphragm with continuous loading path. The second model contained a flexible diaphragm. Dynamic identification tests were performed on each model before and after the experiments in order to identify and track changes in their natural period as the experiments progress. Results showed that the integrity of flooring diaphragm had a considerable impact on improving the seismic performance and reducing the seismic vulnerability of URM buildings with respect to control the damage level and limiting the crack occurred in the model. According to the test results, model with integrated stiff in-plane behavior could meet the Life Safety (LS) performance level. The strengthening methodology on the roof distributed the internal forces more appropriately between different elements and took advantage of the strength of different structural elements.